Salaires et emploi dans les secteurs public et privé. Différences et interactions - Bradley, Jake; Dickson, Matt; Postel-Vinay, Fabien; Turon, Helene (Revue française d’économie, 2016)
Differences in wages and in employment between the public and the private sectors are not only present in a static comparison. Dynamic features of employment such as returns to experience, wage volatility and job security also exhibit differences across the two sectors. In the first part of this paper we document these differences in six European countries over the period 1994-2001 using the European Community Household Panel. This enables us to evaluate lifetime premia offered by public sector employment in these countries. In the second part of the paper we present a structural model of the labour market with a public sector, which allows us to quantify the response of the labour market as a whole to various public sector policies in terms of employment and wages. This structural approach enables us to assess and compare the potential impact of alternative polices aimed at reducing the public sector wage bill.